The role of selective attention in perceptual switching - Stoesz, Brenda M. (2008)
When viewing ambiguous figures, individuals can exert selective attentional control over their perceptual reversibility behaviour (e.g., Strüber & Stadler, 1999). In the current study, we replicated this finding but we also found that ambiguous figures containing faces are processed quite differently from those containing objects. Furthermore, inverting an ambiguous figure containing faces (i.e., Rubin’s vase-face) resulted in an “inversion effect”. These findings highlight the importance of considering how we attend to faces in addition to how we perceive and process faces. Describing the perceptual reversal patterns of individuals in the general population allowed us to draw comparisons to behaviours exhibited by individuals with Asperger Syndrome (AS). The group data suggested that these individuals were less affected by figure type or stimulus inversion. Examination of individual scores, moreover, revealed that the majority of participants with AS showed an atypical reversal pattern, particularly with ambiguous figures containing faces, and an atypical inversion effect. Together, our results show that ambiguous figures can be a very valuable tool for examining face processing mechanisms in the general population and other distinct groups of individuals, particularly those diagnosed with AS.